2010
DOI: 10.1007/s10682-010-9452-8
|View full text |Cite
|
Sign up to set email alerts
|

The potential of a population genomics approach to analyse geographic mosaics of plant--insect coevolution

Abstract: A central issue in the evolutionary ecology of species interactions is coevolution, which involves the reciprocal selection between individuals of interacting species. Understanding the importance of coevolution in shaping species interactions requires the consideration of spatial variation in their strength. This is exactly what the, recently developed, geographic mosaic theory of coevolution addresses. Another major development in the study of population ecology is the introduction of the population genomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…Using the approach of Vermeer et al. (), results suggested that Escalon, Newark, and Upper Lake potentially represent coevolutionary hot spots, while Arbuckle, Linden, and Yuba City potentially represent coevolutionary cold spots. However, Bayesian simulations using BayeScan indicated that none of the potential outliers for either species showed significant ( p < .05) signatures of selection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the approach of Vermeer et al. (), results suggested that Escalon, Newark, and Upper Lake potentially represent coevolutionary hot spots, while Arbuckle, Linden, and Yuba City potentially represent coevolutionary cold spots. However, Bayesian simulations using BayeScan indicated that none of the potential outliers for either species showed significant ( p < .05) signatures of selection.…”
Section: Resultsmentioning
confidence: 99%
“…However, as Vermeer et al. () outline, for this approach to provide more than preliminary evidence for the presence of a geographic mosaic of coevolution, genotype data from a large number of independent neutral loci (preferably single nucleotide polymorphisms [SNPs]) need be compared to phenotypic measurements from traits of interest, as has been done in other systems (e.g., Dupas, Dubuffet, Carton, & Poire, ; Jancek et al., ; Parchman, Benkman, Jenkins, & Buerkle, ; Parchman et al., ). Given that our current study includes genotype data only, and from a relatively small number of microsatellite loci, we are not yet able to determine whether the presence of outlier loci in both species is the result of reciprocal selection, or of random chance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations